DDQ/TBHP-Induced Oxidative Cyclization Process: A Metal-Free Approach for the Synthesis of 2-Phenylquinazolines - Rachakonda, Sridhar; Pratap, P. Surya; Basaveswara Rao, Mandava V. (Synthesis, 2012)
Various 2-phenylquinazoline derivatives were synthesized under metal-free conditions from readily available 2-aminophenyl ketones and benzylamines via condensation and oxidative cyclization using 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) as a versatile reagent. The reaction gave the corresponding 2-phenylquinazoline derivatives in good to excellent yields (up to 92%).
Keywords: 2-aminobenzophenones; 2-aminoacetophenones; benzylamines; 2,3-dichloro-5,6-dicyano-1,4-benzoquinone; 2-phenylquinazolines; oxidative cyclization